Hypofrontality in schizophrenic patients and its relevance for the choice of antipsychotic medication: an event-related potential study - Ehlis, Ann-Christine; Plichta, Michael M. (The world journal of biological psychiatry, 2012)
Objectives. One of the neurobiological core features of schizophrenic illnesses is a hypo-functionality of the frontal cortex (“cerebral hypofrontality”). The two major classes of antipsychotic medication differ regarding their impact on frontal lobe function and metabolism, with a presumably more positive effect of “atypical” compared to “typical” agents. To date, neurobiological markers reliably predicting the treatment response to different antipsychotics are lacking. The present study, therefore, aimed at establishing a neurophysiological marker of frontal lobe function (NoGo-Anteriorization, NGA) as a predictor of the treatment response to first- and second-generation antipsychotics. Methods. Seventy-six schizophrenic patients were examined three times over a 6-week study period. Patients were treated with first- or second-generation antipsychotics, and NGA, neurocognitive performance, and symptomatology were assessed on admission as well as during two follow-up measurements. Results. Baseline NGA values significantly predicted the treatment response to typical and atypical antipsychotics; however, the direction of this prediction was dependent on the antipsychotic drug regimen. Moreover, atypical antipsychotics had a superior impact on neurocognitive performance and self-reported quality of life. Conclusions. The NGA might be a useful tool in developing individualized treatment strategies based on pathophysiological aspects of schizophrenic illnesses that can be easily determined in clinical routine settings.